Potential risk for bacterial contamination in conventional reused ventilator systems and disposable closed ventilator-suction systems. - Ya-Chi Li; Hui-Ling Lin; Fang-Chun Liao; Sing-Siang Wang; Hsiu-Chu Chang; Hung-Fu Hsu; Sue-Hsien Chen; Gwo-Hwa Wan (PLoS ONE, 2018)
Few studies have investigated the difference in bacterial contamination between conventional reused ventilator systems and disposable closed ventilator-suction systems. The aim of this study was to investigate the bacterial contamination rates of the reused and disposable ventilator systems, and the association between system disconnection and bacterial contamination of ventilator systems.The enrolled intubated and mechanically ventilated patients used a conventional reused ventilator system and a disposable closed ventilator-suction system, respectively, for a week; specimens were then collected from the ventilator circuit systems to evaluate human and environmental bacterial contamination. The sputum specimens from patients were also analyzed in this study.The detection rate of bacteria in the conventional reused ventilator system was substantially higher than that in the disposable ventilator system. The inspiratory and expiratory limbs of the disposable closed ventilator-suction system had higher bacterial concentrations than the conventional reused ventilator system. The bacterial concentration in the heated humidifier of the reused ventilator system was significantly higher than that in the disposable ventilator system. Positive associations existed among the bacterial concentrations at different locations in the reused and disposable ventilator systems, respectively. The predominant bacteria identified in the reused and disposable ventilator systems included Acinetobacter spp., Bacillus cereus, Elizabethkingia spp., Pseudomonas spp., and Stenotrophomonas (Xan) maltophilia.Both the reused and disposable ventilator systems had high bacterial contamination rates after one week of use. Disconnection of the ventilator systems should be avoided during system operation to decrease the risks of environmental pollution and human exposure, especially for the disposable ventilator system.ClinicalTrials.gov PRS / NCT03359148.